PENTINGNYA KOMUNIKASI BERBAHASA INGGRIS KEPADA TAMU DI BANQUET SERVICE HOTEL MANDARIN ORIENTAL JAKARTA - Widha Raditia; Ardi Mularsari (Media Bina Ilmiah, 2023)
Banquet service is a service that includes events or activities in a hotel company by providing food and beverage services and includes Dinners, Conferences, and Wedding Parties. This research was conducted at Mandarin Oriental Hotel Jakarta to master one of the foreign languages, especially English so that there is no miss understanding in pronunciation to guests by banquet service at the Mandarin Oriental Jakarta hotel. This English communication plays an important role in Mandarin Oriental Hotel Jakarta, because English communication is a skill that every employee must have, with a good and correct mastery of English communication, the hotel's performance system will be more advanced. The purpose of this study is also to provide English communication services to guests in organizing an event both small and large scale. So that at this time the author can describe that this banquet service is part of the Food and Beverage Department that sells, coordinates and serves the organization of events. The research method that the author used in this study, namely a qualitative method with interview data collection techniques to obtain information from parties related to the topic they want to discuss to the supervisor banquet service and based on the author's ability to connect the facts, information, and data obtained. The results of research developed by the author that English communication is very important in banquet service because it can provide benefits for the progress of the hotel.